Evaluation of Cardiac Dysfunction among Children with Dengue Fever (Bangladesh Journal of Medical Microbiology, 2025)
Background: Evidence is increasing that dengue can also cause myocardial impairment, arrhythmias and, occasionally, fulminant myocarditis. Defining the role of cardiac dysfunction in the haemodynamic compromise of severe dengue has potentially important management implications.Objectives: The aim of this present study was to explore the incidence of cardiac dysfunction in children with dengue infection and to evaluate the features of cardiac involvement with the severity of dengue fever.Methodology: This cross-sectional study was conducted in Department of Paediatrics at Universal Medical College & Hospital, Dhaka, Bangladesh. Children with clinical features suggestive of dengue and further confirmed by dengue NS1 antigen or IgM antibody positivity between the ages of 1 month and 16 years were evaluated. Patients were classified as severe dengue, dengue with/without warning signs as per World Health Organization (WHO) criteria. All included children underwent cardiac assessment in form of clinical examination, cardiac markers, electrocardiograms (ECG) and echocardiograms. Differences in cardiac function were correlated with severity of dengue.Results: Mean age of the patients was 8.5±3.9 years and male: female ratio 2.0:1. Acute onset of fever and severe headache was commonest presentation (100.0%). Duration of fever was 3-5 days in maximum cases (67.7%). On clinic-pathological evaluation dengue fever was categories into three classes. In this study dengue without warning sign was 53(55.2%) cases, dengue with warning sign was detected in 25(26.0%) and severe dengue was 18(18.75%) patients. The most common ECG abnormality was T wave inversion noted in 21.8% of patients, low amplitude QRS complexes in 12 patients and ST depression in 14 patients. Echo findings were normal in 75.0% cases. Ejection Fraction